THE ARCHITECTURAL CHARACTERISTICS LINKAGE OF BATANG KUANTAN’S RUMAH GODANG WITH TANAH DATAR’S RUMAH GADANG - Muhammar Khamdevi (Langkau Betang: Jurnal Arsitektur, 2019)
Riau and West Sumatra have shared history from the days of the Old Malay Kingdom, Sriwijaya, Dharmasraya, Malayupura (Minangkabau), Islamic Sultanates, etc. The traditional house of Rumah Godang in Batang Kuantan region somehow have some similarities to the Rumah Gadang in Tanah Datar. No researcher has tried to discuss the relationship among them. Therefore, this study tries to explore the linkage of their architectural characteristics. This study uses a qualitative method by comparing the architectural characteristics of the two buildings from the data obtained in the field. The results of the study indicates a linkage, even a liniage.